2007
DOI: 10.1177/0887403407302332
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Examination of AMBER Alert's Effects

Abstract: AMBER Alerts are public announcements designed to elicit citizen tips that could help rapidly recover abducted children before they can be harmed by their kidnappers. Using various media accounts as a data source to garner a convenience sample of 275 alerts, the authors gathered basic information, including victim–offender relationship, recovery time, and the direct effects of the alert. AMBER Alert does appear to provide some positive benefits in recovering abducted children, although the evidence suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 16 publications
(21 reference statements)
5
44
0
1
Order By: Relevance
“…Table 1 shows the codings and descriptive statistics for the variables used in the analysis, with missing-data cases included. Prior research on AMBER Alert has shown the importance of the identity of the abductor in predicting the likelihood of successful recovery (Griffin et al, 2007), so for each Alert success story, the Relationship of the abductor to the abducted child is coded. The Alert Effect indicates the manner, if any, in which the Alert facilitated the recovery of the child.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 shows the codings and descriptive statistics for the variables used in the analysis, with missing-data cases included. Prior research on AMBER Alert has shown the importance of the identity of the abductor in predicting the likelihood of successful recovery (Griffin et al, 2007), so for each Alert success story, the Relationship of the abductor to the abducted child is coded. The Alert Effect indicates the manner, if any, in which the Alert facilitated the recovery of the child.…”
Section: Methodsmentioning
confidence: 99%
“…In almost a third of the sample cases the Alerts made some contribution to the recovery of abducted children, but the system was far more likely to be effective where the abductor's motivations were not apparently sinister, such as when the child was taken by a parent in the midst of a custody dispute (Griffin et al, 2007). Furthermore, even "successful" Alerts rarely worked within the narrow window of time (three hours) generally regarded as crucial in cases involving abductors with perverse and cruel intentions, and were in fact least likely to be effective in such cases (apparently-a crucial caveat identified by the researchers is the impossibility of knowing how a kidnapping leading to an AMBER Alert "would have" ended absent the Alert.)…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, this "mission creep" of enacting further policies restricting sex offenders and inclusion of juveniles, some of which are guilty of consensual sex, may run the risk of causing "sex offender notification fatigue" (Griffin et al, 2007). In other words the general public may become desensitized and exhausted by the overload of sex offender information (number of names in registries and new legislation) and ignore the issue entirely.…”
Section: Policy Recommendation #1: Eliminate Community Notification Amentioning
confidence: 99%